Planetary boundary layer evolution over an equatorial Andean valley: A simplified model based on balloon‐borne and surface measurements. (2nd August 2018) - Cazorla, Maria; Juncosa, Julieta
Abstract : Planetary boundary layer (PBL) evolution over a populated Andean valley east of Quito, Ecuador is investigated through an empirical model. Balloon‐borne measurements of boundary layer height (PBLh) were found to correlate strongly ( R 2 = 0.871) as a function of virtual temperature at the surface calculated with 10 min ground station observations. This simplified model captures slow and fast regimes of PBL growth observed from the early morning to midday, which lead to the development of either shallow or deep PBLs. Surface conditions under which different scenarios of PBL develop are discussed in light of a test performed with 2015 station data. The proposed model can be used with the purpose of interpreting air quality measurements. Abstract : PBL height measurements collected at Universidad San Francisco de Quito's Atmospheric Measurement Station (EMA USFQ) correlate strongly with virtual temperature at the surface (10‐min data). Symbols indicate PBLh measurements in meters above ground level (magl) taken at the indicated local time (LT) (UTC ‐ 5) in different months between June 2014 and February 2018. The black line depicts the model function that best fits experimental data (R 2 = 0.871). Error bars are 1‐σ absolute uncertainty in PLBh measurements.